Prolific plant regeneration through organogenesis from scalps of Musa sp cv. Tanduk - Elhory, Suleiman Mohamed Ahmed; Abdul Aziz, Maheran; Abdul Rashid, Azmi; Yunus, Abdul Ghani (Academic Journals, 2009)
A prolific plant regeneration system using scalps derived from shoot tips of Musaspp. cv. Tanduk was developed. Highly proliferating scalps, produced after four monthly subcultures of shoot tip explant on Murashige and Skoog (MS) medium supplemented with 100 mM BAP and 1.0 mM IAA, were placed on MS basal medium supplemented with 1.0, 2.5 and 5.0 mM BAP. Rooting of shoots was assessed on hormone-free half strength and full strength MS media and on MS medium supplemented with 1.0, 5.0 and 10 mM IBA. Four types of potting media comprising of sand, peat, sand + top soil + goat dung (3:2:1 v/v) and top soil + sand (1:1 v/v) were evaluated during acclimatization of the plantlets. Prolific shoot regeneration from scalps was obtained on MS medium containing 2.5 mM BAP, at 9.61 and 40.6 shoots per explant after 4 and 8 weeks of culture, respectively. Meanwhile, the highest mean shoot height of 2.19 cm was attained on MS medium with 1.0 mM BAP after 8 weeks of culture. Full-strength MS medium supplemented with 5.0 mM IBA produced the highest mean number of roots per explant at 15.08, while the highest mean root length of 11.07 cm was obtained on hormone-free half strength MS medium at week 4 of culture. The highest plant survivability of 77.5% was achieved in potting medium consisting of top soil + sand + goat dung after 6 weeks of acclimatization. The plants were morphologically normal with vigorous stems and broad green leaves.